Creative Research in Music Informed Practice, Innovation and Transcendence (Taylor & Francis, 2021)
Creative Research in Music explores what it means to be an artistic researcher in music in the twenty-first century. The book delineates the myriad processes that underpin successful artistic research in music, providing best practice exemplars ranging from Western classical art to local indigenous traditions, and from small to large-scale, multi-media and cross-cultural work formats. Drawing on the richness of creative research work at key institutions in South-East Asia and Australian, this book examines the social, political, historical and cultural driving forces that spur and inspire excellence in creative research to extend and to cross boundaries, to sustain our music industry, to advocate for the importance of music in our world, and to make it clear that music matters. In the chapters, our authors present the ideas of informed practice, innovation and transcendence from diverse international perspectives. Each of these three themes has an introductory section where the theme is explored and the chapters in that section introduced. Taken as a whole, the book discusses how the themes in combination, with reference to the authorial group, are able to transform music pedagogy and performance for our global and complex world.
English
Keywords: Music; Techniques of music / music tutorials; arts research, Australia, creative research, creativity, global music industry, informed practice, ISME, music pedagogy, music research, Oceania, performance, performance practice, Singapore, Southeast Asia, Thailand